Factors Affecting Bank Performance: Empirical Evidence from Morocco - Elouali Jaouad; Oubdi Lahsen (European Scientific Journal, ESJ, 2018)
This study empirically examines the effects of bank-specific characteristics, bank governance, financial market structure, and macroeconomic conditions on Moroccan banks’ performance. Moroccan banks’ performance is measured by return on assets (ROA) and return on equity (ROE). For this aim, panel data method (fixed effects model) is applied to data which is obtained from a sample of 6 Moroccan banks’ financial statements during the period 2010-2016. The findings show that only operating management efficiency represented by the cost-to-income ratio (COST) is highly significant and negatively related to bank’s performance. Also, the results indicate that bank size (SIZE) is positively related to ROA and statistically significant. Nevertheless, the effects of the other variables are statistically insignificant. The findings suggest that future studies could be include more dependent and independent variables to explain Moroccan banks’ performance.